Silicone rubber adhesive with low temperature resistance and high bonding reliability and preparation method of silicone rubber adhesive
By modifying the molecular structure of polysiloxane and tackifier, combining the composite of hydrogen-containing silicone oil and hydrogen-containing silicone resin, the problem of unstable bonding performance of the addition silicone rubber adhesive in low temperature and high and low temperature environments is solved, and high reliability and flexible bonding effects are achieved.
Patent Information
- Application Number
- CN202411954025.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-25
AI Technical Summary
The bonding performance of the addition silicone rubber adhesive is unstable at low temperatures and at high and low temperature alternating environments, and the bonding strength to the substrate is insufficient.
By modifying the molecular structure of the vinyl-terminated polysiloxane and tackifier, it has a low glass transition temperature, a composite of hydrogen-containing silicone oil and hydrogen-containing silicone resin is added as a crosslinking agent, and a small molecular polymer is added as a tackifier to improve bonding strength and flexibility.
It realizes high-reliability bonding at low temperature and high and low temperature alternating environments, improves the bonding strength and flexibility of silicone rubber adhesives, and meets the application requirements in low temperature bending and high and low temperature alternating environments.
Smart Images

Figure CN119875575A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic silicone adhesives, and in particular relates to a low-temperature-resistant and highly reliable bonding silicone rubber adhesive and a preparation method thereof. Background Art
[0002] Due to its unique molecular structure, silicone rubber has excellent properties such as high and low temperature resistance, UV resistance, radiation resistance, and insulation. It is widely used in various technical fields and is an adhesive with the best low-temperature performance.
[0003] Compared with condensation-type silicone rubber adhesives, addition-type silicone rubber adhesives have the advantages of fast curing speed and low curing shrinkage, and have better application prospects in fields requiring good curing dimensional stability and large-area rapid prototyping. However, due to the inert surface of addition-type silicone rubber and poor adhesion to the substrate, it is necessary to further improve the addition-type silicone rubber adhesive system, such as adding a tackifier to improve the bonding strength between it and the substrate. Traditional silane coupling agents, such as KH-560, KH-570, etc., can effectively improve the bonding strength of silicone rubber, but because they will form a brittle interface layer on the surface of the substrate, stress concentration will occur at low temperatures, especially during high and low temperature changes, which is not conducive to the bonding stability and reliability when used at low temperatures and in high and low temperature changes.
[0004] Therefore, how to improve the bonding strength of addition silicone rubber and maintain good bonding performance under low temperature and high and low temperature alternating environments is a research work that needs to be carried out systematically. Summary of the invention
[0005] The present invention aims to provide a low-temperature resistant and highly reliable bonding silicone rubber adhesive and a preparation method thereof, which can meet the use requirements in low-temperature scenes and high-low temperature alternating environments. The molecular structures of vinyl-terminated polysiloxane and tackifier in the adhesive are modified to have a low glass transition temperature, excellent high-low temperature impact resistance and low-temperature flexible bonding performance, and can meet the high-reliability bonding use requirements in low-temperature bending and high-low temperature alternating environments; a compound of hydrogen-containing silicone oil and hydrogen-containing silicone resin is used as a cross-linking agent to effectively improve the bonding strength of the adhesive; a small molecule polymer containing diethylsiloxane, silaneoxy and boron is added as a tackifier to improve the bonding strength of the silicone rubber adhesive while ensuring the low-temperature flexibility of the bonding interface.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] A low-temperature resistant and highly reliable silicone rubber adhesive comprises a component A and a cross-linking agent component B, wherein the component A comprises a base adhesive, a first catalyst, an inhibitor, a tackifier, a reinforcing filler, a filling filler and a radiation-resistant filler; the base adhesive is a vinyl-terminated polysiloxane, and the specific structure is as follows:
[0008]
[0009] Wherein, a, b and c are all integers between 20 and 1000, and c / (a+b+c)≥0.03;
[0010] Preferably, a, b and c are integers between 40 and 800.
[0011] According to an embodiment of the present invention, the molecular weight of the vinyl terminated polysiloxane is 30,000 to 80,000, preferably 40,000 to 60,000.
[0012] According to an embodiment of the present invention, the general structural formula of the tackifier is as follows:
[0013]
[0014] Wherein, R is one of methyl, ethyl, propyl, vinyl, phenyl, methacryloxypropyl, and glycidyloxypropyl;
[0015] R3 is methoxy and / or ethoxy;
[0016] R' is selected from one or more of hydroxyl, methyl, ethyl, propyl, butyl, vinyl, and phenyl;
[0017] M is selected from an integer between 0 and 4;
[0018] Preferably, m is selected from an integer between 1 and 3.
[0019] According to an embodiment of the present invention, the adhesive includes 100 parts of component A and 2 to 5 parts of component B, a crosslinking agent, in parts by mass.
[0020] According to an embodiment of the present invention, the component A includes, by mass, 100 parts of vinyl-terminated polysiloxane, 0.03-0.2 parts of a first catalyst, 0.1-0.5 parts of an inhibitor, 1-3 parts of a tackifier, 10-30 parts of a reinforcing filler, 5-25 parts of a filling filler and 4-10 parts of a radiation-resistant filler.
[0021] According to an embodiment of the present invention, the first catalyst in the A component is a single-component platinum catalyst with a concentration of 1000ppm to 6000ppm, preferably 2000ppm to 5000ppm.
[0022] According to an embodiment of the present invention, the inhibitor is selected from alcohols and / or siloxanes.
[0023] For example, one or more of acetylene cyclohexanol, methyl butynol, tetramethyldivinyldisiloxane or tetramethyltetravinylcyclotetrasiloxane.
[0024] According to an embodiment of the present invention, the reinforcing filler is selected from one or both of hydrophobic fumed silica and hydrophobic precipitated silica.
[0025] According to an embodiment of the present invention, the filling material is selected from one or more of silicon micropowder, cristobalite powder, fused quartz powder, crystalline quartz powder, and aluminum oxide.
[0026] According to an embodiment of the present invention, the radiation-resistant filler is selected from one of ferric oxide, cerium oxide and bismuth oxide.
[0027] According to an embodiment of the present invention, the crosslinking agent B component is a mixture of hydrogen-containing silicone oil and hydrogen-containing silicone resin.
[0028] Preferably, the mass ratio of the hydrogen-containing silicone oil to the hydrogen-containing silicone resin is (1-5):1.
[0029] According to an embodiment of the present invention, the hydrogen content of the hydrogen-containing silicone oil is 0.5 wt % to 1.6 wt %, and the hydrogen content of the hydrogen-containing silicone resin is 0.3 wt % to 0.7 wt %.
[0030] The present invention also provides a method for preparing a low-temperature reliable bonding addition-type silicone rubber adhesive, the steps of which are as follows:
[0031] 1) preparing a base rubber vinyl-terminated polysiloxane and a tackifier;
[0032] 2) mixing the vinyl-terminated polysiloxane, reinforcing filler, filling filler and radiation-resistant filler by stirring and vacuuming, and then kneading them by a three-roll mill;
[0033] 3) After the mixed rubber material is cooled to room temperature, it is placed in a planetary mixer or a kneader, and the first catalyst, inhibitor and tackifier are added and stirred to obtain component A.
[0034] 4) mixing the hydrogen-containing silicone oil and the hydrogen-containing silicone resin in a certain proportion by mechanical stirring to obtain a crosslinking agent component B;
[0035] 5) Fully mix component A and crosslinking agent component B to obtain a low-temperature reliable bonding addition-type silicone rubber adhesive.
[0036] According to an embodiment of the present invention, in the step 2), the mixture is stirred and vacuum mixed by a kneader or a planetary mixer at 120-160° C. for 2-4 hours, and the vacuum degree is controlled below 100 Pa.
[0037] According to an embodiment of the present invention, the material temperature in the planetary mixer or kneader is controlled to be lower than 40°C by external circulating cooling water. According to an embodiment of the present invention, in the step 2), the viscosity of the component A is 25000-50000 mPa·s (23°C). The component A has excellent fluidity and can meet the large-area solvent-free coating process.
[0038] According to an embodiment of the present invention, in step 4), the mass ratio of the hydrogen-containing silicone oil to the hydrogen-containing silicone resin is (1-5):1.
[0039] According to an embodiment of the present invention, the low-temperature flexible silicone rubber structural adhesive has a tensile strength at room temperature greater than 3MPa, an elongation at break greater than 300%, a tensile modulus at room temperature less than 400KPa, an adhesion strength (aluminum-aluminum) greater than 3MPa, and a T peel strength (180°) (PI film-PI fabric) greater than 7N / cm.
[0040] According to an embodiment of the present invention, the preparation method of the vinyl terminated polysiloxane is:
[0041] The raw materials octamethylcyclotetrasiloxane, hexaethylcyclotrisiloxane and octaphenylcyclotetrasiloxane are fully ground and mixed by a sand mill;
[0042] Then, the mixture is put into a polymerization kettle, and a second catalyst (e.g., tetramethylammonium hydroxide alkali gel) and a capping agent (e.g., divinyltetramethyldisiloxane) are added to react to obtain polysiloxane;
[0043] The polysiloxane prepared as above is passed through a short-path distillation device to remove small molecules, because the vinyl-terminated polysiloxane needs to be used in a space environment, so as to meet the use requirements of space-grade silicone rubber.
[0044] According to an embodiment of the present invention, the distillation temperature of the short-path distillation is 220-250° C., the vacuum degree is 1-5 Pa, the total vacuum mass loss of the prepared vinyl-terminated polysiloxane is less than 1%, and the vacuum collectable condensable volatiles are less than 0.1%.
[0045] Among them, octamethylcyclotetrasiloxane and hexaethylcyclotrisiloxane are liquids at room temperature, and octaphenylcyclotetrasiloxane is a crystalline particle. In order to allow the three to be fully mixed, the present application adopts a method different from the traditional preparation method, and chooses to grind with a sand mill in the early stage of polymerization. The product prepared in this way has better heat resistance and better transparency than the polymer directly mixed and prepared by the traditional method, indicating that the distribution of the three siloxanes in the molecular chain is more uniform. The reason is mainly because octaphenylcyclotetrasiloxane is a crystalline particle, and it is of different sizes. The small particle size has better compatibility with octamethylcyclotetrasiloxane and hexaethylcyclotrisiloxane. In the copolymerization process, it is easier to obtain the random distribution of different chain links; and the large particles have poor compatibility with the two, and the reaction speed is also slow, which will cause the prepared copolymer chain link distribution to be unsatisfactory, and as the polymerization viscosity increases, there will be unreacted particles that are coated, causing the final product to be whitish, and the final result is that the three different silicon oxygen chain links are not ideally distributed, which in turn affects the properties such as heat resistance. After grinding with a sand mill, the particle size of octaphenylcyclotetrasiloxane is made smaller and more uniform, and the compatibility of the three raw materials is increased, so that the obtained copolymer has greatly improved chain segment distribution and polymerization degree, and the resulting copolymer has better transparency and heat resistance. In addition, by utilizing the low viscosity characteristics of octamethylcyclotetrasiloxane and hexaethylcyclotrisiloxane, the sand mill grinding process does not require the addition of additional solvents, making the production process simpler and easier to operate.
[0046] According to an embodiment of the present invention, the preparation method of the tackifier comprises:
[0047] S1, after diethyldiethoxysilane and trifluoromethanesulfonic acid are uniformly mixed, a certain amount of acetic acid is added to the mixture when the temperature rises to 50-70°C, and after the addition is completed, the generated by-products are removed by vacuuming, and when no small molecules are evaporated, the reaction is stopped to obtain the product M;
[0048] S2, adding the product A of step S1 dropwise to the boric acid compound, the reaction temperature is 50-70°C, after the addition is completed, vacuum is applied to remove the small molecular byproducts produced by the reaction, and when no small molecules are evaporated, the reaction is stopped to obtain the product N;
[0049] S3, adding product N dropwise into alkoxysilane at a reaction temperature of 50-70°C. After the addition is complete, vacuuming is performed to remove the generated by-products. When no small molecules are evaporated, a weak base is added to terminate the reaction, and the viscosity enhancer is obtained by filtration.
[0050] According to an embodiment of the present invention, the reaction equation of the tackifier is as follows:
[0051]
[0052] Wherein, R3 is one of methoxy and ethoxy;
[0053] R is one of methyl, ethyl, propyl, vinyl, phenyl, methacryloxypropyl, and glycidyloxypropyl;
[0054] R' can be one of hydroxyl, methyl, ethyl, propyl, butyl, vinyl, and phenyl.
[0055] m is an integer between 0 and 4, and preferably m is an integer between 1 and 3.
[0056] In order to construct a flexible bonding interface, the present invention introduces low-temperature flexible ethylsiloxane chain segments into the main chain of the tackifier, and at the same time introduces boron elements to improve the bonding strength by utilizing its electron-deficient effect, and introduces silanoxy groups to react with hydroxyl groups on the surface of the substrate to improve the bonding strength. Because the tackifier needs to have a mobile property, the number of ethylsiloxane chain segments introduced into the molecular chain needs to be strictly controlled.
[0057] According to an embodiment of the present invention, in step S1, the mass of trifluoromethanesulfonic acid added is 1‰ to 3‰ of diethyldiethoxysilane.
[0058] According to an embodiment of the present invention, the molar ratio of diethyldiethoxysilane to acetic acid is (1.1-2):1, preferably (1.2-1.8):1.
[0059] According to an embodiment of the present invention, in step S1, the dropping time is 1 to 4 hours.
[0060] According to an embodiment of the present invention, in step S2, the boronic acid compound is one or more of boric acid, methylboric acid, ethylboric acid, n-propylboric acid, n-butylboric acid, phenylboric acid and vinylboric acid.
[0061] According to an embodiment of the present invention, the molar ratio of the added amount of the boric acid compound to the amount of diethyldiethoxysilane in step S1 is 2:(1-5).
[0062] According to an embodiment of the present invention, in step S2, the dropping time is 0.5 to 2 hours.
[0063] According to an embodiment of the present invention, in step S3, the alkoxysilane is one of γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, phenyltrimethoxysilane and phenyltriethoxysilane.
[0064] According to an embodiment of the present invention, the molar ratio of the amount of the alkoxysilane added to the amount of the boric acid compound added in step S2 is (1-2):1.
[0065] According to an embodiment of the present invention, in step S3, the dropping time is 1 to 4 hours.
[0066] According to an embodiment of the present invention, in step S3, the time for terminating the reaction is 1 to 2 hours.
[0067] According to an embodiment of the present invention, the weak alkaline substance is one of sodium bicarbonate, sodium carbonate, ammonium bicarbonate and calcium carbonate.
[0068] The present invention also provides an application of the above-mentioned low-temperature resistant and highly reliable bonding silicone rubber adhesive in low-temperature and high-low-temperature alternating environments, which has bonding stability and reliability.
[0069] Beneficial effects of the present invention:
[0070] 1) The present invention designs the molecular structure of vinyl-terminated polysiloxane and improves the polymerization process to produce a ternary copolymer polysiloxane with better heat resistance and transparency, which can meet the requirements of ultra-low temperature flexibility and low volatility in space environments.
[0071] 2) The present invention designs the molecular structure of the tackifier to prepare a polysiloxane oligomer containing diethylsiloxy chain segments, silaneoxy groups, and boron elements. The electron-deficient nature of the boron atom, the low-temperature characteristics of the diethoxysiloxy chain segments, and the hydrolysis reaction of the silaneoxy groups are utilized to enhance the interfacial bonding strength of the silicone rubber while achieving low-temperature flexibility and bendability.
[0072] 3) The silicone rubber adhesive prepared by the present invention has excellent working time, low viscosity, low modulus and high bonding properties. The working time is greater than 24 hours, and it can be completely cured in 30 to 60 minutes at 100 to 150°C, which can meet the continuous production and rapid curing molding process; the tensile strength at room temperature is greater than 3MPa, the elongation at break is greater than 300%, the tensile modulus at room temperature is less than 400KPa, the bonding strength (aluminum-aluminum) is greater than 3MPa, and the T peel strength (180°) (PI film-PI fabric) is greater than 7N / cm, which can meet the large-area molding process of solar wing flexible substrates as well as the low-temperature flexibility and bonding reliability requirements.
[0073] 4) The preparation method of the present invention not only has cheap and readily available raw materials, but also has a simple production process and is easy to operate. At the same time, the reaction conditions are mild and there is no special requirement for equipment, so it is easy to realize industrialization. DETAILED DESCRIPTION
[0074] The present invention will be described in further detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0075] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available.
[0076] Example 1
[0077] Preparation of vinyl terminated polysiloxanes
[0078] The raw materials octamethylcyclotetrasiloxane, hexaethylcyclotrisiloxane and octaphenylcyclotetrasiloxane were mixed and then put into a sand mill for thorough grinding and mixing for 30 minutes, and then put into a polymerization kettle, and the second catalyst tetramethylammonium hydroxide alkali gel and the end-capping agent divinyltetramethyldisiloxane were added. After stirring and reacting at 120°C for 5 hours, the temperature was raised to 160°C and stirring was continued for 2 hours to obtain crude vinyl-terminated polysiloxane products with different viscosities and different phenyl and ethyl contents.
[0079] The prepared vinyl-terminated polysiloxane crude product was distilled 6 times in a short-path distillation device at 220-250°C and a vacuum degree of 1-5 Pa to obtain a vinyl-terminated polysiloxane product with a volatile content reaching a space-grade level. The specific product properties are shown in Table 1.
[0080] Comparative Example 1
[0081] The difference from Example 1 is that when preparing the vinyl-terminated polysiloxane, the raw materials are not put into the sand mill for sufficient grinding and mixing.
[0082] The raw materials octamethylcyclotetrasiloxane, hexaethylcyclotrisiloxane and octaphenylcyclotetrasiloxane, the second catalyst tetramethylammonium hydroxide alkali gel and the end-capping agent divinyltetramethyldisiloxane were added into a polymerization kettle. After stirring and reacting at 120°C for 8 hours, the temperature was raised to 160°C and stirring was continued for 2 hours to prepare a crude vinyl-terminated polysiloxane.
[0083] The prepared vinyl terminated polysiloxane crude product was distilled 6 times in a short-path distillation device at 220-250° C. and a vacuum degree of 1-5 Pa to obtain a vinyl terminated polysiloxane product. The specific product properties are shown in Table 1.
[0084] Table 1
[0085]
[0086]
[0087] It can be seen from the data in Table 1 that when the raw materials octamethylcyclotetrasiloxane, hexaethylcyclotrisiloxane and octaphenylcyclotetrasiloxane are ground by a sand mill, the particle size of octaphenylcyclotetrasiloxane is smaller and more uniform, and the compatibility of the three raw materials is increased, so that the obtained copolymer has a more ideal distribution in the chain segments, so the appearance and thermal properties of the vinyl-terminated polysiloxane prepared by polymerization are better than those of the polymerization product not ground by a sand mill.
[0088] Example 2
[0089] Preparation of viscosity enhancer
[0090] 1) In a three-necked flask equipped with a mechanical stirrer, under nitrogen protection, 100 g of diethyldiethoxysilane and 0.15 g of trifluoromethanesulfonic acid were added respectively, and after stirring evenly, the temperature was raised to 55° C., and 18.9 g of acetic acid was added dropwise. The addition was completed in 2 hours, and the vacuum degree was controlled at 200 Pa. The generated by-products were removed by vacuuming. When no small molecules were evaporated, the reaction was stopped;
[0091] 2) adding the product prepared in step 1) dropwise to 35.1 g of boric acid, setting the temperature to 55° C. for 1 hour, and after the addition is complete, controlling the vacuum degree at 300 Pa, and evacuating until no small molecules evaporate to stop the reaction;
[0092] 3) The product prepared in step 2) was added dropwise to 201 g of γ-glycidyloxypropyltrimethoxysilane, the temperature was set to 60°C, the dropping time was 2 hours, after the dropping was completed, the vacuum degree was controlled at 200 Pa, and vacuum was applied until no small molecules were evaporated, 0.058 g of calcium carbonate was added, stirring was continued for 2 hours, and then filtration was performed to obtain thickener-1.
[0093] Example 3
[0094] 1) In a three-necked flask equipped with a mechanical stirrer, under nitrogen protection, 100 g of diethyldiethoxysilane and 0.20 g of trifluoromethanesulfonic acid were added respectively, and after stirring evenly, the temperature was raised to 60° C., and 18.9 g of acetic acid was added dropwise. The addition was completed in 2 hours, and the vacuum degree was controlled at 200 Pa. The generated by-products were removed by vacuuming. When no small molecules were evaporated, the reaction was stopped;
[0095] 2) adding the product prepared in step 1) dropwise to 33.95 g of methylboric acid, setting the temperature to 60° C. for 1.5 hours. After the addition is complete, the vacuum degree is controlled at 200 Pa, and the reaction is stopped by evacuating until no small molecules evaporate;
[0096] 3) The product prepared in step 2) was added dropwise to 140.9 g of γ-methacryloxypropyltrimethoxysilane, the temperature was set to 60° C., the dropping time was 2 hours, after the dropping was completed, the vacuum degree was controlled at 300 Pa, and vacuum was applied until no small molecules were evaporated, 0.085 g of sodium carbonate was added, stirring was continued for 2 hours, and then filtration was performed to obtain thickener-2.
[0097] Example 4
[0098] 1) In a three-necked flask equipped with a mechanical stirrer, under nitrogen protection, 100 g of diethyldiethoxysilane and 0.25 g of trifluoromethanesulfonic acid were added respectively, and after stirring evenly, the temperature was raised to 70° C., and 24.3 g of acetic acid was added dropwise. The addition was completed in 1 hour, and the vacuum degree was controlled at 200 Pa. The generated by-products were removed by vacuuming. When no small molecules were evaporated, the reaction was stopped;
[0099] 2) adding the product prepared in step 1) dropwise to 27.94 g of ethylboric acid, setting the temperature to 60° C. for 1.5 hours. After the addition is complete, the vacuum degree is controlled at 200 Pa, and the reaction is stopped by evacuating until no small molecules evaporate;
[0100] 3) The product prepared in step 2) was added dropwise to 71.97 g of vinyltriethoxysilane, the temperature was set to 60° C., the dropping time was 3 hours, after the dropping was completed, the vacuum degree was controlled at 200 Pa, and vacuum was applied until no small molecules were evaporated, 0.15 g of sodium bicarbonate was added, stirring was continued for 2 hours, and then filtration was performed to obtain tackifier-3.
[0101] Example 5
[0102] 1) In a three-necked flask equipped with a mechanical stirrer, under nitrogen protection, 100 g of diethyldiethoxysilane and 0.25 g of trifluoromethanesulfonic acid were added respectively, and after stirring evenly, the temperature was raised to 55° C., and 24.3 g of acetic acid was added dropwise. The addition was completed in 3 hours, and the vacuum degree was controlled at 400 Pa. The generated by-products were removed by vacuuming. When no small molecules were evaporated, the reaction was stopped;
[0103] 2) adding the product prepared in step 1) dropwise to 27.18 g of vinylboric acid, setting the temperature to 70° C. for 2 hours, and after the addition is complete, controlling the vacuum degree at 300 Pa, and evacuating until no small molecules evaporate to stop the reaction;
[0104] 3) The product prepared in step 2) was added dropwise to 51.51 g of methyltrimethoxysilane, the temperature was set to 50° C., the dropping time was 4 hours, after the dropping was completed, the vacuum degree was controlled at 300 Pa, and vacuum was applied until no small molecules were evaporated, 0.15 g of sodium bicarbonate was added, stirring was continued for 2 hours, and then filtration was performed to obtain tackifier-4.
[0105] Example 6
[0106] 1) In a three-necked flask equipped with a mechanical stirrer, under nitrogen protection, 100 g of diethyldiethoxysilane and 0.3 g of trifluoromethanesulfonic acid were added respectively, and after stirring evenly, the temperature was raised to 50° C., and 27.3 g of acetic acid was added dropwise. The addition was completed in 4 hours, and the vacuum degree was controlled at 200 Pa. The generated by-products were removed by vacuuming. When no small molecules were evaporated, the reaction was stopped;
[0107] 2) adding the product prepared in step 1) dropwise to 34.58 g of phenylboric acid, setting the temperature to 70° C. for 2 hours. After the addition is complete, the vacuum degree is controlled at 200 Pa, and the reaction is stopped by evacuating until no small molecules evaporate;
[0108] 3) The product prepared in step 2) was added dropwise to 54.54 g of ethyltriethoxysilane, the temperature was set to 70° C., the dropping time was 3 hours, after the dropping was completed, the vacuum degree was controlled at 300 Pa, and vacuum was applied until no small molecules were evaporated, 0.18 g of sodium bicarbonate was added, stirring was continued for 2 hours, and then filtration was performed to obtain tackifier-5.
[0109] The preparation of the low temperature resistant and highly reliable bonding silicone rubber adhesive of the present invention is as follows:
[0110] Adhesive Example 1
[0111] Preparation of component A of low temperature resistant and highly reliable silicone rubber adhesive:
[0112] 100 kg of the vinyl-terminated polysiloxane-1 prepared in Example 1 was weighed and added to a planetary mixer, 30 kg of hydrophobic fumed silica, 10 kg of silicon powder (4000 mesh), and 5 kg of ferric oxide were weighed and added to the planetary mixer, and vacuum kneaded at 130° C. for 4 hours, with the vacuum degree controlled at 80 Pa, and then mixed three times by a three-roll mill; then added to the planetary mixer, cooled to room temperature, and then 50 g of a single-component platinum catalyst (concentration 5000 ppm), 500 g of tetramethyl divinyl disiloxane and 1 kg of tackifier-1 were added, and stirring was continued for 2 hours (the material temperature in the planetary mixer was controlled to be lower than 40° C. by external circulating cooling water), to obtain component A. The viscosity of the material is 25000 mPa·s (23° C.).
[0113] Preparation of component B of silicone rubber adhesive:
[0114] 1 kg of hydrogen-containing silicone oil (hydrogen content 0.5%) and 1 kg of hydrogen-containing silicone resin (hydrogen content 0.3%) were weighed and mechanically mixed for 1 hour to obtain component B.
[0115] When in use, the above-mentioned component A and component B are mixed in a mass ratio of 100:4.5 to obtain a low-temperature reliable bonding addition-type silicone rubber adhesive.
[0116] After curing at 100℃ for 60min, the tensile strength, bonding strength (aluminum-aluminum), and T peel strength (PI film-PI fabric) were tested. The composite PI film-PI fabric samples were subjected to 90° bending test at -196℃, high and low temperature impact test (-155℃~+150℃, 500 cycles), appearance after electron irradiation (400keV electron radiation source, flux 1.5×1015e / cm2) and 180° T peel test at room temperature. The performance data are shown in Table 2.
[0117] Adhesive Example 2
[0118] Preparation of component A of silicone rubber adhesive:
[0119] 100 kg of the vinyl-terminated polysiloxane-2 prepared in Example 1 was weighed and added to a kneader, 20 kg of hydrophobic fumed silica, 15 kg of quartz powder (6000 mesh), and 4 kg of cerium oxide were weighed and added to the kneader, and vacuum kneaded at 140° C. for 3 hours, with the vacuum degree controlled to 90 Pa, and then mixed three times by a three-roll mill; then added to the kneader, cooled to room temperature, and then 100 g of a single-component platinum catalyst (concentration 3000 ppm), 400 g of tetramethyltetravinylcyclotetrasiloxane and 2 kg of tackifier-2 were added, and stirring was continued for 2 hours (the material temperature in the planetary mixer was controlled to be lower than 40° C. by external circulating cooling water), to obtain component A. The viscosity of the material is 30000 mPa·s (23° C.).
[0120] Preparation of component B of the silicone rubber adhesive: 1 kg of hydrogen-containing silicone oil (hydrogen content 0.7%) and 0.5 kg of hydrogen-containing silicone resin (hydrogen content 0.5%) were weighed and mechanically mixed for 1 hour to obtain component B.
[0121] When used, weigh the above-mentioned component A and component B according to the mass ratio of 100:3, mix them, and after curing at 120℃ for 60 minutes, test the tensile strength, bonding strength (aluminum-aluminum), and T peel strength (PI film-PI fabric). The composite PI film-PI fabric samples were subjected to 90° bending test at -196℃, high and low temperature impact test (-155℃~+150℃, 500 cycles), appearance after electron irradiation (400keV electron radiation source, flux 1.5×1015e / cm2) and 180° T peel test at room temperature. The performance data are shown in Table 2.
[0122] Adhesive Example 3
[0123] Preparation of component A of silicone rubber adhesive:
[0124] 80kg of vinyl-terminated polysiloxane-3 and 20kg of vinyl-terminated polysiloxane-1 were weighed and added to a kneader, 20kg of hydrophobic precipitated silica, 10kg of fused quartz powder (6000 mesh), 10kg of crystalline quartz powder (4000 mesh), and 6kg of bismuth oxide were weighed and added to the kneader, and vacuum kneaded at 150°C for 2 hours, with the vacuum degree controlled at 60Pa, and then mixed three times by a three-roll mill; then added to the kneader, cooled to room temperature, and then 200g of a single-component platinum catalyst (concentration 2000ppm), 100g of methyl butynol and 2.5kg of tackifier-3 were added, and stirring was continued for 2 hours (the material temperature in the planetary mixer was controlled to be lower than 40°C by external circulating cooling water), to obtain component A. The viscosity of the material is 35000mPa·s (23°C).
[0125] Preparation of component B of the silicone rubber adhesive: 1 kg of hydrogen-containing silicone oil (hydrogen content 1.2%) and 0.3 kg of hydrogen-containing silicone resin (hydrogen content 0.7%) were weighed and mechanically mixed for 1 hour to obtain component B.
[0126] When used, the above-mentioned components A and B are mixed in a mass ratio of 100:2.5, and after curing at 150°C for 40 minutes, the tensile strength, bonding strength (aluminum-aluminum), and T peel strength (PI film-PI fabric) are tested. The composite PI film-PI fabric samples are subjected to a 90° bending test at -196°C, a high and low temperature impact test (-155°C to +150°C, 500 cycles), and an appearance test after electron irradiation (400keV electron radiation source, flux 1.5×1015e / cm2) and a 180° T peel test at room temperature. The performance data are shown in Table 2.
[0127] Adhesive Example 4
[0128] Preparation of component A of the silicone rubber adhesive: 30 kg of vinyl-terminated polysiloxane-5, 20 kg of vinyl-terminated polysiloxane-4, and 50 kg of vinyl-terminated polysiloxane-1 were weighed and added to a planetary mixer, 15 kg of hydrophobic fumed silica, 15 kg of silicon powder (6000 mesh), 10 kg of aluminum oxide (4000 mesh), and 8 kg of ferric oxide were weighed and added to the planetary mixer, and vacuumed and stirred at 160° C. for 2 hours, with the vacuum degree controlled at 70 Pa, and then mixed three times by a three-roll grinder; then added to the planetary mixer, cooled to room temperature, and then 80 g of a single-component platinum catalyst (concentration 5000 ppm), 100 g of acetylene cyclohexanol, 1 kg of tackifier-1, and 1 kg of tackifier-5 were added, and stirring was continued for 2 hours (the material temperature in the planetary mixer was controlled to be lower than 40° C. by external circulating cooling water) to obtain component A. The viscosity of the material is 40000 mPa·s (23°C).
[0129] Preparation of component B of the silicone rubber adhesive: 1 kg of hydrogen-containing silicone oil (hydrogen content 1.6%) and 0.2 kg of hydrogen-containing silicone resin (hydrogen content 0.5%) were weighed and mechanically mixed for 1 hour to obtain component B.
[0130] When using, take the above-mentioned component A and component B in a ratio of 100:2 and mix them. After curing at 150℃ for 60 minutes, test the tensile strength, bonding strength (aluminum-aluminum), and T peel strength (PI film-PI fabric). The composite PI film-PI fabric samples were subjected to a 90° bending test at -196℃, a high and low temperature impact test (-155℃~+150℃, 500 cycles), and electron irradiation (400keV electron radiation source, flux 1.5×1015e / cm 2 ) and 180° T peel test at room temperature. The performance data are shown in Table 2.
[0131] Adhesive Comparative Example 1
[0132] Preparation of component A of silicone rubber adhesive: 100 kg of vinyl-terminated polysiloxane-1 prepared in Example 1 was weighed and added to a planetary mixer, 30 kg of hydrophobic fumed silica and 10 kg of silicon powder (4000 mesh) were weighed and added to the planetary mixer, vacuum kneaded at 130°C for 4 hours, and the vacuum degree was controlled to 80 Pa, and then mixed three times by a three-roll mill; then added to the planetary mixer, cooled to room temperature, and then 50 g of a single-component platinum catalyst (concentration 5000 ppm), 500 g of tetramethyl divinyl disiloxane and 1 kg of tackifier-1 were added, and stirring was continued for 2 hours (the material temperature in the planetary mixer was controlled to be lower than 40°C by external circulating cooling water), to obtain component A. The viscosity of the material is 24500 mPa·s (23°C).
[0133] Preparation of component B of the silicone rubber adhesive: 1 kg of hydrogen-containing silicone oil (hydrogen content 0.5%) and 1 kg of hydrogen-containing silicone resin (hydrogen content 0.3%) were weighed and mechanically mixed for 1 hour to obtain component B.
[0134] When using, take the above-mentioned component A and component B in a ratio of 100:4.5 and mix them. After curing at 100℃ for 60 minutes, test the tensile strength, bonding strength (aluminum-aluminum), and T peel strength (PI film-PI fabric). The composite PI film-PI fabric samples were subjected to a 90° bending test at -196℃, a high and low temperature impact test (-155℃~+150℃, 500 cycles), and electron irradiation (400keV electron radiation source, flux 1.5×1015e / cm 2 ) and 180° T peel test at room temperature. The performance data are shown in Table 2.
[0135] Adhesive Comparative Example 2
[0136] Preparation of component A of silicone rubber adhesive: 100 kg of vinyl-terminated polysiloxane-1 was weighed and added to a planetary mixer, 30 kg of hydrophobic fumed silica, 10 kg of silica powder (4000 mesh), and 5 kg of ferric oxide were weighed and added to the planetary mixer, and vacuum kneaded at 130°C for 4 hours, with the vacuum degree controlled at 80 Pa, and then mixed three times by a three-roll mill; then added to the planetary mixer, cooled to room temperature, and then 50 g of a single-component platinum catalyst (concentration 5000 ppm), 500 g of tetramethyl divinyl disiloxane, and 1 kg of γ-glycidyl ether oxypropyl trimethoxy silane were added, and stirring was continued for 2 hours (the material temperature in the planetary mixer was controlled to be lower than 40°C by external circulating cooling water), and component A was obtained. The viscosity of the material is 25000 mPa·s (23°C).
[0137] Preparation of component B of the silicone rubber adhesive: 1 kg of hydrogen-containing silicone oil (hydrogen content 0.5%) and 1 kg of hydrogen-containing silicone resin (hydrogen content 0.3%) were weighed and mechanically mixed for 1 hour to obtain component B.
[0138] When used, take the above-mentioned component A and component B in a ratio of 100:4.5 and mix them. After curing at 100℃ for 60 minutes, test the tensile strength, bonding strength (aluminum-aluminum), and T peel strength (PI film-PI fabric). The composite PI film-PI fabric samples were subjected to a 90° bending test at -196℃, a high and low temperature impact test (-155℃~+150℃, 500 cycles), and an electron irradiation test (400keV electron radiation source, flux 1.5×1015e / cm 2 ) and 180° T peel test at room temperature. The performance data are shown in Table 2.
[0139] Table 2. Performance data of adhesive examples 1-4 and adhesive comparative examples 1-2
[0140]
[0141] From the test data in Table 2, it can be seen that the low-temperature reliable bonding addition-type silicone rubber adhesive obtained by using the tackifier prepared by the present invention can obtain a polyimide composite sample with excellent T peel strength, and the sample also has excellent low-temperature flexibility, and can still maintain structural integrity and excellent T peel strength after bending at low temperature and high and low temperature impact.
[0142] In Comparative Example 2, when a single coupling agent (KH-560) was used as a tackifier, although it had certain bonding strength and T-peel strength at room temperature, after high and low temperature impact tests and low temperature bending, the bonding strength and T-peel strength were greatly reduced, and the overall structure of the sample cracked and debonded. In Comparative Example 1, the sample without radiation resistance additives had a significant decrease in T-peel strength after electron irradiation.
[0143] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A low temperature resistant and highly reliable bonding silicone rubber adhesive, characterized in that: It comprises component A and component B, a crosslinking agent; the component A comprises a base rubber, a first catalyst, an inhibitor, a tackifier, a reinforcing filler, a filling filler and a radiation-resistant filler; the base rubber is a vinyl-terminated polysiloxane, and the general structural formula is as follows: Wherein, a, b and c are all integers between 20 and 1000, and c / (a+b+c)≥0.03; Preferably, a, b and c are integers between 40 and 800.
2. The silicone rubber adhesive according to claim 1, characterized in that: The general structural formula of the tackifier is as follows: Wherein, R is one of methyl, ethyl, propyl, vinyl, phenyl, methacryloxypropyl, and glycidyloxypropyl; R3 is methoxy and / or ethoxy; R' is selected from one or more of hydroxyl, methyl, ethyl, propyl, butyl, vinyl, and phenyl; M is selected from an integer between 0 and 4; Preferably, m is selected from an integer between 1 and 3.
3. The silicone rubber adhesive according to claim 1, characterized in that: The composition comprises 100 parts of component A and 2 to 5 parts of crosslinking agent component B according to weight parts; Preferably, in parts by mass, the component A comprises: 100 parts of vinyl-terminated polysiloxane, 0.03-0.2 parts of a first catalyst, 0.1-0.5 parts of an inhibitor, 1-3 parts of a tackifier, 10-30 parts of a reinforcing filler, 5-25 parts of a filling filler and 4-10 parts of a radiation-resistant filler.
4. The silicone rubber adhesive according to claim 1, characterized in that: The viscosity of component A at 23° C. is 25,000 to 50,000 mPa·s; Preferably, the first catalyst in the component A is a single-component platinum catalyst with a concentration of 1000ppm to 6000ppm, more preferably 2000ppm to 5000ppm; Preferably, the molecular weight of the vinyl terminated polysiloxane is 30,000 to 80,000, preferably 40,000 to 60,000.
5. The silicone rubber adhesive according to claim 1, characterized in that: The crosslinking agent B component is a mixture of hydrogen-containing silicone oil and hydrogen-containing silicone resin; Preferably, the mass ratio of the hydrogen-containing silicone oil to the hydrogen-containing silicone resin is (1-5):1; Preferably, the hydrogen content of the hydrogen-containing silicone oil is 0.5wt% to 1.6wt%, and the hydrogen content of the hydrogen-containing silicone resin is 0.3wt% to 0.7wt%.
6. The silicone rubber adhesive according to claim 1, characterized in that: The inhibitor is selected from alcohols and / or siloxanes; for example, one or more of acetylene cyclohexanol, methyl butynol, tetramethyl divinyl disiloxane or tetramethyl tetravinyl cyclotetrasiloxane.
7. The silicone rubber adhesive according to claim 1, characterized in that: The reinforcing filler is selected from one or both of hydrophobic fumed silica and hydrophobic precipitated silica; Preferably, the filler is selected from one or more of silicon powder, cristobalite powder, fused quartz powder, crystalline quartz powder, and aluminum oxide; Preferably, the radiation-resistant filler is selected from one or more of ferric oxide, cerium oxide, and bismuth oxide.
8. A method for preparing the low temperature resistant and highly reliable bonding silicone rubber adhesive according to any one of claims 1 to 7, characterized in that: include: 1) preparing a base rubber vinyl-terminated polysiloxane and a tackifier; 2) mixing the vinyl-terminated polysiloxane, reinforcing filler, filling filler and radiation-resistant filler by stirring and vacuuming, and then kneading them by a three-roll mill; 3) After the mixed rubber material is cooled to room temperature, it is placed in a planetary mixer or a kneader, and the first catalyst, inhibitor and tackifier are added and stirred to obtain component A; 4) mixing the hydrogen-containing silicone oil and the hydrogen-containing silicone resin in a certain proportion by mechanical stirring to obtain a crosslinking agent component B; 5) Fully mix component A and crosslinking agent component B to obtain a low-temperature reliable bonding addition-type silicone rubber adhesive. Preferably, in the step 2), the mixture is stirred and vacuumed by a kneader or a planetary mixer at 120 to 160° C. for 2 to 4 hours, and the vacuum degree is controlled below 100 Pa; Preferably, the mass mixing ratio of the hydrogen-containing silicone oil to the hydrogen-containing silicone resin is (1-5):
1.
9. The preparation method according to claim 8, characterized in that: The steps of preparing the vinyl terminated polysiloxane include: The raw materials octamethylcyclotetrasiloxane, hexaethylcyclotrisiloxane and octaphenylcyclotetrasiloxane are fully ground and mixed by a sand mill; The mixed raw materials are fed into a polymerization kettle, and a second catalyst (e.g., tetramethylammonium hydroxide alkali gel) and a capping agent (e.g., divinyltetramethyldisiloxane) are added to react to obtain polysiloxane; The polysiloxane is subjected to short-path distillation to remove small molecules, thereby meeting the use requirements of space-grade silicone rubber; Preferably, the distillation temperature of the short-path distillation is 220-250° C., the vacuum degree is 1-5 Pa, the total vacuum mass loss of the prepared vinyl-terminated polysiloxane is less than 1%, and the condensable volatiles that can be collected in vacuum are less than 0.1%.
10. The preparation method according to claim 8, characterized in that: The preparation method of the tackifier comprises: S1, after diethyldiethoxysilane and trifluoromethanesulfonic acid are uniformly mixed, a certain amount of acetic acid is added to the mixture when the temperature rises to 50-70°C, and after the addition is completed, the generated by-products are removed by vacuuming, and when no small molecules are evaporated, the reaction is stopped to obtain the product M; S2, adding the product A of step S1 dropwise to the boric acid compound, the reaction temperature is 50-70°C, after the addition is completed, vacuum is applied to remove the small molecular byproducts produced by the reaction, and when no small molecules are evaporated, the reaction is stopped to obtain the product N; S3, adding the product N dropwise to the alkoxysilane at a reaction temperature of 50-70°C. After the addition is complete, vacuuming is performed to remove the generated by-products. When no small molecules are evaporated, a weak base is added to terminate the reaction, and the tackifier is obtained by filtration; The reaction equation of the tackifier is as follows: Wherein, R3 is one of methoxy and ethoxy; R is one of methyl, ethyl, propyl, vinyl, phenyl, methacryloxypropyl, and glycidyloxypropyl; R' can be one of hydroxyl, methyl, ethyl, propyl, butyl, vinyl, and phenyl. m is an integer between 0 and 4, and preferably m is an integer between 1 and 3. Preferably, in step S1, the mass of trifluoromethanesulfonic acid added is 1‰ to 3‰ of diethyldiethoxysilane; Preferably, the molar ratio of diethyldiethoxysilane to acetic acid is (1.1-2):1, preferably (1.2-1.8):1; Preferably, in step S2, the boronic acid compound is one or more of boric acid, methylboric acid, ethylboric acid, n-propylboric acid, n-butylboric acid, phenylboric acid and vinylboric acid; Preferably, the molar ratio of the amount of the boric acid compound added to the amount of diethyldiethoxysilane in step S1 is 2:(1-5); Preferably, in step S3, the alkoxysilane is one of γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, phenyltrimethoxysilane and phenyltriethoxysilane; Preferably, the molar ratio of the amount of the alkoxysilane added to the amount of the boric acid compound added in step S2 is (1-2):
1. Preferably, the weakly alkaline substance is one of sodium bicarbonate, sodium carbonate, ammonium bicarbonate and calcium carbonate.